Study methodology to promote a non-traditional material into a construction material for transportation infrastructures and geotechnical works. The example of the processed steel slags of national iron steel companies. - Ferreira, S. (2012)
In Portugal, and also at international level, preventing the production of a significant number of different types of waste, where are included the steel slags is still unfeasible. Therefore, there is strong pressure to use industrial byproducts and recycled materials in the construction of transportation infrastructure and geotechnical works. The reuse of these materials positively affects the environment by reducing deposits and preserving raw materials. This paper presents the study methodology involving the environmental and geomechanical characterization and field monitoring that was used for evaluating the application of Portuguese processed steel slags in transportation infrastructures and geotechnical works. From the test results it was concluded that these materials fulfill the requirements of the Specification of the Portuguese Roads Administration based in empirical tests. It was also concluded that performance laboratory tests results show a much better material performance than the results based in empirical tests (Los Angeles and micro-Deval). In addition, this material when compared with results of mechanical tests of natural unbound granular materials used in road construction show better mechanical performance. These test results prove that the mechanical laboratory properties must be determined by performance laboratory tests, once the empirical tests could not predict the real mechanical behavior of these materials. Additionally, leaching test results show that this byproduct is inert and became titled “Inert Steel Aggregates for Construction (ISAC)”. These laboratory conclusions were validated in a full-scale field trial, where were used raw materials and ISAC, by end performance testing.